2002
DOI: 10.14295/ras.v16i1.1303
|View full text |Cite
|
Sign up to set email alerts
|

Contaminação Da Água Subterrânea Por Nitrato No Parque Ecologico Do Tietê - São Paulo, Brasil

Abstract: The aim of this study is to investigate groundwater contamination caused by septic tank, which infiltrates domestic effluent into a sandy-alluvial unconfined aquifer at Parque Ecológico do Tietê (São Paulo, Brasil). The methodology used is based on chemical analysis of 68 shallow monitoring wells (up to 5.0 deep) installed at 50x50m area. Some chemical parameters as nitrate, nitrite, ammonium, chloride, pH, Eh, electric conductivity and dissolved oxygen have been measured fortnightly using portable equipaments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 2 publications
0
7
0
15
Order By: Relevance
“…In the inland areas of Brazil, these septic tanks are often constructed without adequate technical and sanitary standards. Varnier and Hirata (2002) identified a strong and negative correlation between the Cl -concentration of groundwater and the distance between the wells and the septic tanks. Palácio et al (2008) and Andrade et al (2009) further verified that anthropogenic pollution causes the Cl -concentration in groundwater to increase.…”
Section: + )mentioning
confidence: 97%
See 1 more Smart Citation
“…In the inland areas of Brazil, these septic tanks are often constructed without adequate technical and sanitary standards. Varnier and Hirata (2002) identified a strong and negative correlation between the Cl -concentration of groundwater and the distance between the wells and the septic tanks. Palácio et al (2008) and Andrade et al (2009) further verified that anthropogenic pollution causes the Cl -concentration in groundwater to increase.…”
Section: + )mentioning
confidence: 97%
“…When the water samples were collected from the well, it was noticed that Figure 4 -Precipitation and temporal variability of NO 3 -in wells in A1 (B) and A2 (C) small domestic animals like chickens and pigs were raised nearby and that there was a septic tank less than 15 m away. Previous studies have shown that the groundwater in wells is easily contaminated by unsanitary septic tanks in the vicinity, especially in areas where the local soil is sandy (ANDRADE et al, 2009;HELENA et al, 2000;VARNIER;HIRATA, 2002).…”
Section: Nitrate Ionmentioning
confidence: 99%
“…O aquífero local é caracterizado como livre, de porosidade primária, heterogêneo e anisotrópico, associado aos sedimentos quaternários e também aos materiais de aterro sobrejacentes. Este aquífero pode apresentar uma espessura média de até dezenas de metros, conectando-se hidraulicamente com os sedimentos terciários da BSP (VARNIER & HIRATA, 2002).…”
Section: áRea De Estudounclassified
“…A contaminação das águas subterrâneas com íons de nitrato está relacionada com o processo de lixiviação, por causa de sua alta mobilidade e estabilidade nos sistemas aeróbios de águas subterrâneas e, ao longo do tempo, pode haver considerável incremento dos teores de nitrato das águas do lençol freático (Varnier & Hirata, 2002;Scanlon et al, 2010).…”
Section: Similaridade Hidroquímicaunclassified